INTERNAL FACTOR OF MSMEs IN THE POST-PANDEMIC COVID-19 : OBSTACLES OR DETERMINANTS FOR BUSINESS SUSTAINABILITY - Lelimawarti, Anis; Afkar, Taudlikhul (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2024)
The strength of MSMEs during the Covid-19 pandemic really tested their business continuity. Internal factors such as capital, quality of human resources, business networks, mentality of business actors, and transparency are determinants in maintaining business sustainability to develop businesses to become more resilient. The purpose of this research is to show that these internal factors are obstacles or determinants of the sustainability of MSMEs post-pandemic Covid-19. The sampling technique in this research used stratified random sampling by classifying the number of MSMEs in 5 regions in Surabaya. The data collection technique uses survey via questionnaire with 200 respondents who are divided according to the proportion of the number of MSMEs in each region. Data analysis using SEM-PLS. The findings of this research show that capital, quality of human resources, business networks are determining factors in the sustainability of MSMEs with dominance in the capital factor, while transparency is a determining factor in the decline of MSMEs. The next findings show that the mentality of business actors is an obstacles factor in the sustainability of MSMEs